Penguatan Literasi Digital dan Cross-Cultural Understanding bagi Generasi Z di SMP Kristen Satya Wacana - Tunjung Wijanarka; Dewi Kartika Sari; Agnes Angelica Marshelli Dheyadika; Zefania Maria Hutabarat (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to stregthen the digital literacy and cross-cultural understanding (CCU) os students at Satya Wacana Christian Junior High School as part of Generation Z, a group that is particularly vulnerable to hoaxes and disinformation in the digital democratic sphere. The program was implemented through a participatory training approach that combined interactive lectures, hoax simulations, groups discussions, and pre-test and post-test evaluations using Google Forms. The results indicate an improvement in participants’ ability to distinguish between hoaxes, misinformation, and disinformation, as well as increased awareness of the importance of information verification and tolerant attitudes toward cultural differences. These findings support Joseph DeVito’s theory of perception regararding the role of media stimulus in shaping perceptions and are also relevant to Jurgen Habermas’s concept of the deliberative public sphere. This program contributes a contextual, measurable, and easily replicable CCU-based digital literacy training model to support inclusive digital democracy.